TEACHING MATERIALS OF INDONESIAN LANGUAGE BASED ON COMPETENCE - Hasibuan, Ahmad Laut; Harahap, Rosmawati; Harahap , Nurhayati (Advances in Social Sciences Research Journal, 2021)
pMany experiences show that the students’ achievement in Indonesian language is far from being satisfactory.nbsp;nbsp; nbsp;The results of the 2018 national examination nbsp;showed decrease. Decreasing the results of national examination of Indonesian subjects requires a systematic effort to improve the students competencenbsp; of the national examination on the future. The research aims atnbsp;nbsp;nbsp;nbsp;nbsp;nbsp; developing nbsp;materials teaching of Indonesian language based on competence for high school students. This study uses a research amp; development design conductednbsp; in three cycles, namelynbsp; (1) a preliminary study to observe the ability of high school students, 2) planning includes the activities of deciding objectives, nbsp;competency formulation, both core and basic competencies, material for each competency, and learning and evaluation steps. (3) the development of teaching materials and validated by experts. The validation result of competency-based Indonesian teaching materialnbsp; is nbsp;good. This shows that the appropriateness of its content is in accordance with the module and students' needs, the element of language has fulfilled the element of readability and has clarity of information, the presentation has fulfilled the elements of clarity of purpose and systematicism, and the graphic uses the specified fone.nbsp;/p